Effects of salinity and food on growth and survival rate of mangrove snail (\(Nerita balteata\) Reeve, 1885) at the spat larvae stage - Vu, Trong Dai; Pham, Thi Khanh; Mai, Nhu Thuy; Ho, Son Lam (Vietnam Journal of Marine Science and Technology, 2021)
Mangrove snail (Nerita balteata) belongs to gastropoda species distributed in the coastal intertidal and offshore islands of Quang Ninh province. Although the artificial seeds production of this species have been successful but still having a bottle neck as a low survival rate in the process by veliger larvae are transformed into spat larvae stage. Experiments were conducted to determine effects of salinity and food on growth rate and survival rate of mangrove snail in the stage of spat larvae in Quang Ninh province. The results showed that the optimal salinity for growth and developtment of spat larvae was 25‰ that resulted in a absoluted growth rate of 16.5 ± 2.19 µm/day and survival rate of 26.5 ± 0.57% and significantly higher compared to other treatments. The diet of benthic microalgae (Navicula sp.) combined with formulated feed (AP0 and Frippak) were most suitable for the growth and development of mangrove snail at the spat larvae stage with absoluted growth rate of 25,7 ± 1,28 µm/day; Whereas the survival rate of larvae of 32,3 ± 2,52% was significantly higher than those in the other treatments.